Targeting Wnt/EZH2/microRNA-708 signaling pathway inhibits neuroendocrine differentiation in prostate cancer - Jingxuan Shan (14152608) (2019)
Prostate cancer (PC) castration resistance has been linked to the differentiation of PC luminal cells into hormone-refractory neuroendocrine (NE) cells. However, the molecular mechanisms controlling the emergence of lethal NE prostate cancer (NEPC) remain unclear. The present study aimed to investigate the mechanisms underlying the transition from prostate adenocarcinoma to NEPC. The microRNA miR-708 was involved in NE differentiation and was downregulated in NEPC cells and tumor specimens. miR-708 targeted Sestrin-3 to inhibit Forkhead Box O1 (FOXO1) phosphorylation, resulting in apoptosis of prostate adenocarcinoma cells and AKT-inactivated NEPC cells, the latter of which was consistent with the progression of tumor xenografts in mice under miR-708 treatment. In silico analysis of PC and NEPC tumor specimens suggested that the polycomb repressive complex subunit Enhancer of zeste homolog 2 (EZH2) was particularly overexpressed in NEPC. Notably, EZH2 bound to the miR-708 promoter and induced its silencing in NEPC. Inhibition of EZH2 prevented NE differentiation of PC cells. EZH2 expression was regulated by both Cyclin Dependent Kinase 1 (CDK1) and Wnt signaling. Silencing transcription factor 4 (TCF4), as a key protein in Wnt signaling, prevented NEPC formation. These results provide a molecular basis for the roles of miR-708 and EZH2 in NE differentiation in PC and highlight a new paradigm in NEPC formation and survival. Other Information Published in: Cell Death Discovery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1038/s41420-019-0218-y